IMPLEMENTING DIRECTED READING ACTIVITY (DRA) STRATEGY IN IMPROVING READING COMPREHENSION ABILITY - Sri Maladewi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to improve students' reading comprehension ability through DRA strategy. This study was conducted by using classroom action research at grade I involving 28 students. The results of this study revealed that during the observation in Cycle I meeting I, teachers’ activities was in low category with a score of 10 or 50.00%. Then, the score increased to 12 or 60.00% in meeting II Cycle I with sufficient category. Moreover, in Cycle II meeting I, the score of teacher's activity increased to 15 or 75.00% with good category, and in meeting II, again it increased 17 or 85.00% with very good category. In addition, this study also found that the students’ reading comprehension ability before implementing DRA strategy was 39.29 with incomplete category. After implementing DRA strategy, the average score of classical completeness increased to 50 with incomplete category. After conducting the reflection on learning in cycle I, the results of students’ completeness reached 79 with complete category even though it was not in accordance with the high target of improvement.